Moody Margaretʹs makeover - Simon, Francesca (London : Orion Children's Books, 2013)
When Henry finds out moody margaret is giving her friends makeovers for money, he's sure he can do better. It can't be that hard to make people amazing... can it?
Shelving Location Readers Section. Fiction Book Section
Keywords: English - fiction; Early Readers